GERAKAN PEMBARUAN SAYID AHMAD KHAN - Gunawan B. Dulumina (State Institute of Islamic Studies (IAIN) Palu, 2005)
Sayid Ahmad Khan is an Islamic modernist of India. He is a typical figure who is very enthusiastic in combating illiteracy of Muslims of India. Therefore, he tries to reinterpret the Islamic doctrines in accordance with the development of science and technology. However, because of his radical Islamic thought, he has to accept criticism from conservative Muslims of India. This article tries to discuss his steps in encouraging Muslims of India to positively welcome modernism ideas.Kata kunci : Pembaruan, Sayid Ahmad Khan, Islam